2015
DOI: 10.1177/1352458515586088
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological correlates of multiple sclerosis across the lifespan

Abstract: Neurobiology of pediatric and adult MSThe few pathological studies of pediatric MS suggest that it shares many features with the adult disease. As in adult MS, myelin and axonal damage have also been found in normal-appearing intrahemispheric, interhemispheric, and projection white matter tracts. 9 Despite some remyelination after an attack, over time neurological functioning is permanently decreased due to irreversible axonal injury, depletion of oligodendrocytes, and gliosis. 10 Notably, a recent study has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 105 publications
2
16
0
1
Order By: Relevance
“…13 Other studies comparing children with POMS and adult patients with AOMS also showed lower prevalence rates of depression and fatigue in the first group. 1 This is an interesting finding because higher depression and fatigues scores in adult POMS compared to AOMS patients might be expected, due to the reported association with higher physical disability 26,27 and recent report of an association between psychiatric morbidity and cognitive dysfunction in POMS. 28 We can hypothesize that these patients could develop better coping strategies, due to living with the diagnosis since early age.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…13 Other studies comparing children with POMS and adult patients with AOMS also showed lower prevalence rates of depression and fatigue in the first group. 1 This is an interesting finding because higher depression and fatigues scores in adult POMS compared to AOMS patients might be expected, due to the reported association with higher physical disability 26,27 and recent report of an association between psychiatric morbidity and cognitive dysfunction in POMS. 28 We can hypothesize that these patients could develop better coping strategies, due to living with the diagnosis since early age.…”
Section: Discussionmentioning
confidence: 73%
“…4 The most affected cognitive domains in the paediatric population with MS are similar to those observed in adults, with a predominant involvement of memory, complex attention, information processing speed, executive functions and visual-spatial abilities. [3][4][5][6] Additionally, in POMS subjects, there is accumulating evidence of involvement of linguistic faculties 1,6 and lower intellectual efficiency in terms of intelligence quotient (IQ), particularly in those with younger age at MS onset. 7 An early MS disease onset can have a negative influence in school achievements and overall quality of life, [8][9][10][11] but it is unclear if it could lead to an increased risk for CI in later life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rater differences were evident, with self-reported cognitive fatigue associated with impaired problem solving, while parent-reported cognitive fatigue was associated with impaired verbal learning, cognitive flexibility, and comprehension. By contrast, several authors have found minimal evidence for a relationship between subjective fatigue (either self- or parent-reported) and objective cognitive functioning [51,52,53].…”
Section: Cognitive and Psychosocial Outcomesmentioning
confidence: 99%
“…The pathogenic mechanisms underlying the neuropsychiatric and cognitive disorders in PedMS are not fully understood yet; they may be the result of the irreversible impact that inflammation (demyelination) and/or neurodegeneration produce on the ongoing maturation of the cognitive pathways (Amato et al, 2004(Amato et al, , 2007Di Filippo, Portaccio, Mancini, & Calabresi, 2018). This should be particularly plausible for the language skills that are more commonly involved in PedMS than in adult patients (Nunan-Saah, Paulraj, Waubant, Krupp, & Gomez, 2015).…”
Section: Introductionmentioning
confidence: 99%